Non ST-segment elevation myocardial infarction in patient with essential thrombocythemia - Alioglu, Emin (BioMed Central, 2009)
A 68-year-old woman presented with acute chest pain and a greatly increased platelet count. Cardiac catheterization revealed subtotal occlusion and a thrombus-like filling defect in the right coronary artery. The patient was successfully treated with intravenous tirofiban. Essential thrombocythemia was diagnosed based on bone marrow findings, clinical presentation and laboratory analysis. The relationship between intracoronary thrombus and essential thrombocythemia is discussed.